Inhibitory Effect of Trimidox on Lipopolysaccharide-Induced Nitric Oxide Production in RAW 264.7 Macrophages - Syu-ichi Kanno; Mai Kakuta; Yasue Kitajima; Yuu Osanai; Kaori Kurauchi; Takaharu Ohtake; Mayuko Ujibe; Kouji Uwai; Mituhiro Takeshita; Masaaki Ishikawa (Elsevier, 2007)
We examined the effect of trimidox (3,4,5-trihydroxybenzamidoxime) on the production of nitric oxide (NO) by lipopolysaccharide (LPS) in mouse RAW 264.7 macrophages. Trimidox (50 - 300 µM) concentration-dependently inhibited NO production by LPS (0.01, 0.1, or 1 µg/ml) after incubation for 24 h. LPS-induced expression of inducible NO synthase (iNOS) and degradation of IκBα were prevented by trimidox. The protective effect against NO production by LPS was not only observed in prior incubation but also later incubation with trimidox until iNOS was activated by LPS. These results suggest that trimidox has a predominantly protective effect against LPS-induced production of NO via iNOS expression. Keywords:: trimidox, nitric oxide, macrophage